Pest categorisation of Monema flavescens - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Monema flavescens (Lepidoptera, Limacodidae), following the commodity risk assessment of Acer palmatum plants grafted on A. davidii from China, in which M. flavescens was identified as a pest of possible concern to the European Union. This species can be identified by morphological taxonomic keys and by barcoding. The adults of the overwintering generation emerge from late June to late August. The eggs are laid in groups on the underside of the host‐plant leaves, on which the larvae feed throughout their six to eight larval instars. Pupation occurs in ovoid cocoons at the junction between twigs and branches, or on the trunk. Overwintering occurs as fully grown larvae or prepupae in their cocoon. There are one or two generations per year. M. flavescens is polyphagous and feeds on broadleaves; it has been reported on 51 plant species belonging to 24 families. It mainly occurs in Asia (Bhutan, China, the Democratic People's Republic of Korea, Japan, Nepal, the Republic of Korea), Russia (Eastern Siberia) and Taiwan. It is also present in the USA (Massachusetts). The pest's flight capacities are unknown. The main pathway for entry and spread is plants for planting with cocoons attached. This is partially closed by prohibition of some hosts. In several EU member states climatic conditions are conducive for establishment and many host plants are widespread. Introduction of M. flavescens may result in defoliations influencing tree health and forest diversity. The caterpillars also have urticating spines affecting human health. Phytosanitary measures are available to reduce the likelihood of entry, establishment and spread, and there is a definite potential for classical biological control. Recognising that natural enemies prevent M. flavescens being regarded as a pest in Asia, there is uncertainty regarding the magnitude of potential impact in EU depending on the influence of natural enemies. All criteria assessed by EFSA for consideration as a potential quarantine pest are met.